Razplinjanje prahov pred zgoščevanjem - Bizjak, Milan (Kovine zlitine tehnologije, 1997)
The application of rapid solidification technology (RST) methods for the preparation of metal powders, strips and flakes, followed by their consolidation enable the manufacturing of Al-Fe-X alloys, as well as gedasing (evacuation) of metal containers field with metal ribons/powders is anlysed with Auger spectroscopy. An example of defects formed during hot extrusion of non-evacuated containers is also shown.
Keywords: zlitine; aluminij; aluminum; železo; oksidne plasti; razplinjevanje